2006
DOI: 10.1158/1055-9965.epi-05-0991
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Enterolignans Are Associated with Lower Colorectal Adenoma Risk

Abstract: Lignans are biphenolic compounds that occur in foods of plant origin such as whole grains, seeds, fruits and vegetables, and beverages, such as coffee and tea. Plant lignans are converted by intestinal bacteria into the enterolignans, enterodiol and enterolactone. Enterolignans possess several biological activities, whereby they may influence carcinogenesis. We studied the associations between plasma enterolignans and the risk of colorectal adenomas in a Dutch case-control study. Colorectal adenomas are consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 34 publications
4
49
2
1
Order By: Relevance
“…To our knowledge, this is the only other study of colorectal cancer and phytoestrogen biomarkers that has been published; its overall conclusion is congruent with the results of the present study. A retrospective study reported a decreased likelihood of colorectal adenomas, the precursors to colorectal cancer, among those with higher serum enterodiol levels, and a near-significant trend of decreasing OR values across enterolactone quartiles upon exclusion of antibiotic users (P = 0.05), but is not appropriate for comparison with the present results due to substantial differences in study design and end points (30). The strengths of the present study include the breadth of data available for controlling potential confounders, and its prospective design, thus avoiding bias among cases for their biomarker samples and questionnaire on dietary and questions on health behavior.…”
Section: Discussioncontrasting
confidence: 64%
“…To our knowledge, this is the only other study of colorectal cancer and phytoestrogen biomarkers that has been published; its overall conclusion is congruent with the results of the present study. A retrospective study reported a decreased likelihood of colorectal adenomas, the precursors to colorectal cancer, among those with higher serum enterodiol levels, and a near-significant trend of decreasing OR values across enterolactone quartiles upon exclusion of antibiotic users (P = 0.05), but is not appropriate for comparison with the present results due to substantial differences in study design and end points (30). The strengths of the present study include the breadth of data available for controlling potential confounders, and its prospective design, thus avoiding bias among cases for their biomarker samples and questionnaire on dietary and questions on health behavior.…”
Section: Discussioncontrasting
confidence: 64%
“…A significant concentration of enterolactone has been reported in bovine milk (Antignac et al, 2004). In general, under normal dietary conditions, enterolactone is the enterolignan that reaches the highest concentration in plasma (Kuijsten et al, 2006;Högger, 2013) and is the most effective metabolite in the inhibition of cell proliferation (Corsini et al, 2010;Azrad et al, 2013). Owing to the potential beneficial effects of enterolactone and the complex relationship between the colonic environment and other factors contributing to systemic exposure of such compounds to ABC transporters, a study of the interaction of ABCG2 with enterolactone could be of particular relevance.…”
mentioning
confidence: 99%
“…A growing body of evidence suggests that SDG and its metabolites, in particular EL, may exert protective effects against cancers such as prostate, breast and colon cancer 22,31,43,44 , CVD 26,28 , inflammation 45 , and oxidative damage through diverse mechanisms including phytoestrogenic 46 and antioxidant effects 47 from both in vitro and in vivo studies. Epidemiological studies also suggest that the lower risk of the aforementioned chronic diseases is greatly attributed to high circulating concentrations of EL [48][49][50][51] . Hence, as the promising bioactive form of lignan, the health benefits, mechanisms of the biological effects as well as the pharmacokinetic properties of EL will be discussed below.…”
Section: Production Of Enterolignansmentioning
confidence: 99%